ANALISIS PENGARUH FAKTOR FUNDAMENTAL PERUSAHAAN TERHADAP RISIKO SISTEMATIS (BETA) SAHAM PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 - NAFI KURNIA PUTRI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to obtain empirical evidence about the influence of the firm's fundamental factors on the systematic risk as reflected by the beta value of shares. The fundamental factors of the company have the proxyof cyclicality, operating leverage, financial leverage, current ratio, and assets growth, with firm size as the controlling variable. The population of this study is state-owned companies listed on the Indonesia StockExchange (IDX) in the period from 2014 to 2017. The samples consisted of 13 companies with four years of observation; thus the total samples are 52. Data analysis was performed with the classical assumptionsand hypothesis testing using linear regression. The results of this study indicated that only the variable of operating leverage and the controlling variable of firm size affect the stock beta value. Meanwhile, the variablesof cyclicality, financial leverage, current ratio, and assets growth do not have a significant impact on the stock beta value. The results of this study are expected to be a consideration for investors in making investment decisions related to stock beta value measurement. Key words: systematic risk, stock beta, cyclicality, operating leverage, financial leverage, current ratio, liquidity, assets growth.